Dreams and gestalt therapy - Vásquez, Francisco (2003)
The dream is described here by in the course of the time and the meaning it has and had according to time and culture. The general theory of dreams is focused from Hippocrates until our days, as well as its psychological, religious and cultural interpretation. Emphasis is made on the therapeutic function of dreams, in the Freudian, Jungian and gestalt therapy. It meditates on Freud’s, Jung’s and Perls’ contributions, enlarging the concepts of dream in the gestalt therapy that considers the dream “as the real road to integration, as the human is but a spontaneous production of existence. A dream is the expression that we receive without intention, will and desire. The absurd dream does not impact us in the same moment as something absurd, but he/she feels it as true. The dream is much more than a not concluded desire, it is a very clear existential message about what is missing in our lives, what is avoided to make and live”. The essay is illustrated with a dream work with a patient at the “Guillermo Almenara” Hospital Day Clinic using the gestalt technique. The rehearsal is bounded to an appreciation of the gestalt philosophy and practice on dreams.